The Philosophy of Consciousness: Understanding the Mind-Body Problem - Nurlatipah Nurlatipah; Li Wei; Zhang Li (Yayasan Adra Karima Hubbi, 2024)
Background. The background of this research is based on a long debate between dualism, which separates the mind as a non-physical entity, and materialism, which sees full consciousness as the result of physical processes in the brain. Purpose. The purpose of this study is to explore an integrative approach that tries to bring these two views together to provide a more comprehensive understanding of consciousness. Method. The research method used is a qualitative approach with in-depth literature analysis, involving the thoughts of leading philosophers and neuroscientists. Results. The results show that the integrative approach has the potential to explain the subjective and physical aspects of consciousness simultaneously, without having to set aside one perspective. Conclusion. The conclusion of this study suggests that mind-body problems require a more cross-disciplinary and inclusive approach, which is able to bridge the gap between philosophy and neuroscience. These findings pave the way for more applicable follow-up research to test the validity of integrative approaches in a variety of practical contexts.